Treatment sequencing for the care of patients with advanced or metastatic non-small cell lung cancer in the United States. (4th March 2021) - Hess, Lisa M.; Cui, Zhanglin Lin; Li, Xiaohong Ivy; Molife, Cliff; Oton, Ana B.
Abstract: Objectives: Therapeutic advances for the treatment of patients with advanced/metastatic non-small cell lung cancer (NSCLC) have led to additional options for care. This observational study was designed to describe emerging treatment patterns and survival outcomes. Materials and methods: Flatiron Health's oncology electronic health records database was to identify eligible patients who were age 18+ who initiated second-line therapy for NSCLC Survival analyses were conducted using Kaplan Meier methods and Cox proportional hazard model using SAS 9.4. both unadjusted and adjusted, using generalized propensity score, to account for imbalances between groups. Results: The 10, 060 eligible patients from Dec 2014 to Feb 2019 were 52.6% male; mean age 67.1 years; 70.3% white; 26.0% squamous/70.0% non-squamous (4.1% not specified); and 92.7% were treated at community practices. Immune checkpoint inhibitors (ICIs) were used by 79.9% of the cohort during any line of therapy; 12.1% and 53.7% used ICIs during first- and second-line therapy, respectively. There was heterogeneity in treatment sequencing, as the three most common first→second line sequences accounted for 7.7% (carboplatin + paclitaxel→nivolumab), 5.0% (carboplatin + pemetrexed→nivolumab), and 3.8% (carboplatin + nab-paclitaxel→nivolumab) of the total population, respectively. Unadjusted median overall survival was 21.1 months (95% confidence interval, CI: 20.5–21.6) from metastatic diagnosis. Median survival was 23.0 months (95% CI, 22.3–23.6) for non-squamous and 18.1 months (95% CI, 17.3–18.8) for squamous disease. Conclusion: There is heterogeneity in sequencing strategies that limit the ability to conduct robust comparative effectiveness research of treatment sequences. Since few patients follow a similar treatment trajectory, comparative effectiveness research will be challenged to identify treatment sequences with sufficient sample size.